The Travel—Obesity Connection: Discerning the Impacts of Commuting Trips with the Perspective of Individual Energy Expenditure and Time Use. (August 2013) - Yang, Jiawen; French, Steven
It has been widely reported that individual travel has significant implications for obesity. In this research we try to clarify the connection between travel and obesity from an individual energy-expenditure perspective. It is hypothesized here that individual travel affects the likelihood of becoming obese not only directly through a reliance on automobile-based travel that requires low amounts of individual energy expenditure, but also indirectly through the fatigue and stress stemming from driving, which reduces time available for physical activities and exercise. We use the American Time Use Survey (http://www.bls.gov/tus/ ) for 2003–08 and its Eating and Health Module for 2006 and 2007 to examine individual travel, energy expenditure, and obesity. Empirical analysis illustrates how individual body mass index (BMI) and individual travel are correlated and how this correlation can be explained from the perspective of individual energy expenditure. In addition, a distinction is drawn between commuting and noncommuting trips: Commuting trips have a relatively larger impact on individual BMI. Analysis results point to a potential to reduce obesity rates through planning efforts at the regional level.